PENGARUH MOTIVASI DAN KOMITMEN TERHADAP PENINGKATAN PRESTASI KERJA GURU - Bahrudi Efendi Damanik (Politeknik Bisnis Indonesia, 2019)
This study aims to determine the effect of motivation on improving teacher performance, knowing the effect of teacher commitment on improving teacher performance, knowing the influence of motivation and commitment of teachers to improve teacher performance. This study can be classified in the type of associative descriptive research, namely a complete description of information about the relationship between variables one with symptoms. The total sampling technique for sampling, the sample of this study was 30 people, namely the entire population. The results of this study are that the motivation variable has a positive effect on improving teacher achievement, with t count> t table (1,846> 1,697). Teacher commitment variables have a positive effect on increasing teacher achievement, with tcount> t table (3,217> 1,697). Motivational variables and teacher commitment positively influence teacher performance improvement, with Fcount> Ftable, which is 10.250> 3.320. Obtained r2 (RSquare) of 0.432, it can be seen that the determinant value is 43.20%, which means that the motivation variable and teacher commitment affect teacher performance simultaneously by 43.20%, and the remaining 56.80%, influenced by other factors. factors not checked